2004
DOI: 10.1113/jphysiol.2003.058255
|View full text |Cite
|
Sign up to set email alerts
|

Oncotic pressures opposing filtration across non‐fenestrated rat microvessels

Abstract: We hypothesized that ultrafiltrate crossing the luminal endothelial glycocalyx through infrequent discontinuities (gaps) in the tight junction (TJ) strand of endothelial clefts reduces albumin diffusive flux from tissue into the 'protected region' of the cleft on the luminal side of the TJ. Thus, the effective oncotic pressure difference (σ∆π) opposing filtration is greater than that measured between lumen and interstitial fluid. To test this we measured σ∆π across rat mesenteric microvessels perfused with alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
238
2
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(260 citation statements)
references
References 36 publications
10
238
2
10
Order By: Relevance
“…They found that when the concentration of albumin on the outside of the vessel equalled that on the inside, the effective oncotic gradient from the lumen of the vessel to the interstitium was 70% of that when there was no surrounding albumin: the classic Starling equation predicts that there should be no pressure difference. This finding was termed the 'colloid osmotic pressure (COP) paradox' [2,15,16].…”
Section: Physiology Of the Endothelial Surface Layermentioning
confidence: 99%
See 2 more Smart Citations
“…They found that when the concentration of albumin on the outside of the vessel equalled that on the inside, the effective oncotic gradient from the lumen of the vessel to the interstitium was 70% of that when there was no surrounding albumin: the classic Starling equation predicts that there should be no pressure difference. This finding was termed the 'colloid osmotic pressure (COP) paradox' [2,15,16].…”
Section: Physiology Of the Endothelial Surface Layermentioning
confidence: 99%
“…Adamson et al helped to answer this question [16] by infusing albumin into non-fenestrated microvessels. They found that when the concentration of albumin on the outside of the vessel equalled that on the inside, the effective oncotic gradient from the lumen of the vessel to the interstitium was 70% of that when there was no surrounding albumin: the classic Starling equation predicts that there should be no pressure difference.…”
Section: Physiology Of the Endothelial Surface Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Together with circulating substances, it forms a barrier that prevents circulating cells and macromolecules from entering the interstitium. In contrast to the original Starling model, which explained regulation of fluid balance occurring across the entire endothelial cell, a revised model has been proposed, whereby the hydrostatic and osmotic forces act only across the EGL surface layer on the luminal aspect of the endothelium [31]. These forces reach equilibrium very quickly, resulting in a much lower fluid flux than predicted by the traditional Starling equation (Fig.…”
Section: Revised Starling Equation and The Endothelial Glycocalyxmentioning
confidence: 99%
“…However, in vitro and in vivo deviations from the classic Starling principle have been noted [28], such as absence of the venous reabsorption [29] and lymphatic flow [30] required to prevent interstitial edema, and lack of importance of the interstitial colloid osmotic pressure in determining transendothelial fluid balance [31]. This led to further investigation into non-Starling mechanisms of barrier regulation involving the endothelial glycocalyx layer (EGL) [32].…”
Section: Revised Starling Equation and The Endothelial Glycocalyxmentioning
confidence: 99%